Training Programmes in Sustainable Forest Management in Austria, Croatia and Slovenia - Silvija Krajter Ostoić; Patrick Huber; Marta Curman; Bernhard Wolfslehner; Robert Jandl; Nevenka Bogataj; Todora Rogelja; Andrej Breznikar; Nike Krajnc; Karolina Horvatinčić; Sanja Tišma; Mateja Horvatič; et al. (South-East European Forestry, 2017)
Background and Purpose: During the Erasmus+ project “Cooperation for Innovative Approach in Sustainable Forest Management Training (CIA2SFM)” a study of the existing vocational education and training (VET) and lifelong learning (LLL) programmes in the field of sustainable forest management (SFM) was conducted in Austria, Croatia and Slovenia. The aim of this paper is to get an overview of and analyse SFM-related VET and LLL programmes in the study area, with an emphasis on the identification of good practice examples and providing recommendations for improvement. Materials and Methods: A combined approach of literature review, Internet search and consultations with training providers was applied in order to collect data on training programmes conducted in the period 2006-2015 in Austria, Croatia and Slovenia. The programmes were analysed based on topics, types of methods used, existence of specified learning outcomes, programme evaluation by participants and how the programme was advertised. The analysis employed basic descriptive statistics. Topics were grouped into broader themes. Only training programmes targeting private forest owners, forestry professionals, and forestry entrepreneurs were analysed. Three examples of good practice in each country were selected based on collaboratively developed criteria. Results: In Austria, Croatia and Slovenia numerous training courses related to SFM were conducted in the analysed period, predominantly addressing target groups in forestry sector and covering a variety of topics. The relative importance of themes varied among countries. In order to facilitate the knowledge uptake by participants various methods were applied. Although indoor ex-cathedra approaches prevailed, it could be recognized that there is a growth in interest for foster demonstrations in the field, organizing field trips, emphasize on practical work and combining methods and approaches in most countries. Conclusions: Even if national providers of training programmes may relate to individual needs within national forestry sectors, SFM-related training programmes should be regularly screened and updated according to international agendas and emerging issues. In order to cope with increasing uncertainty and expanding risks forest ecosystems are facing, it is an important task to open up the recent training offer to innovative forms of learning, combinations of topics and learning environments.